Construction of Geosynthetic–Reinforced Pavements and Evaluation of Their Impacts - Danrong Wang; Sheng-Lin Wang; Susan Tighe; Sam Bhat; Shunde Yin (Applied Sciences, 2023)
Geosynthetic materials (i.e., geogrids, geotextiles and other geocomposites) act as an interlayer system and are widely used in construction applications. In pavement structures, geosynthetic layers provide potential benefits such as reinforcement, reflective cracking mitigation, increased fatigue life, and improved drainage and filtering. However, few studies have addressed the installation and construction practices of geosynthetics in pavements. Furthermore, the study of geosynthetics and their contribution during construction are limited. In this paper, a full-scale field study was conducted and three trial sections were constructed; two types of geosynthetics, a fibreglass geogrid and a geogrid composite, were installed in the asphalt binder course and at the interface between the subgrade and base layer, respectively, to be compared with a control section without geosynthetic reinforcement. Trial sections were instrumented to monitor the pressure applied on the subgrade, the strain in the base lift of the asphalt binder course, the temperature, and the moisture within the pavement structure during construction. In addition, post-construction field testing was performed to measure the stiffness of the pavements after construction. The results indicated that geosynthetic-reinforced pavements can maintain pavement resilience during construction and significantly mitigate the disturbances caused by construction activities. The geogrid embedded in the asphalt layer was demonstrated to reduce the pressure at the subgrade caused by paving equipment by 70% compared with the control section, while simultaneously reducing the longitudinal and transverse strain at the bottom of the asphalt layer by 54% and 99%. Observations from the geogrid composite test section also demonstrate the potential to minimize the impacts of future freeze–thaw at the subgrade due to the improved drainage and indirect insulation effect.